Meta Ads as a Mediating Variable in the Relationship Between Consumer Behavior and Engagement to Enhance Marketing Performance at Hotel Cross Paasha Bali Seminyak - Suputra, I Putu Krisna Giridhara; Mahadipta, Ngurah Gede Dwi; Ramayu, I Made Satrya; Pratama, Putu Yogi Agustia (Amkop Management Accounting Review (AMAR), 2026)
This study examines the role of Meta Ads as a mediating variable in the relationship between consumer behavior and engagement in the context of digital marketing at Hotel Cross Paasha Bali Seminyak. The research applies a quantitative approach using a causal associative design, supported by qualitative insights to strengthen the analysis. Data were collected from 120 respondents who are active social media users and have interacted with the hotel’s digital content. The analysis was conducted using Partial Least Squares (PLS). The findings reveal that consumer behavior has a positive and significant effect on both Meta Ads effectiveness and consumer engagement. Furthermore, Meta Ads demonstrate a strong positive influence on engagement and serve as a significant mediating variable between consumer behavior and engagement. These results indicate that personalized, relevant, and interactive digital advertising enhances consumer involvement and strengthens brand relationships. The study contributes to the literature by providing empirical evidence on the mediating role of Meta Ads in the hospitality industry, emphasizing the importance of data-driven digital strategies to improve marketing performance and customer engagement. Keywords: consumer behavior, Meta Ads, engagement, digital marketing, hospitality industry.